How do you evaluate int [x / sqrt (2x-1)]dx for [1, 5]?

3 Answers
Jun 18, 2018

16/3.

Explanation:

Let, I=int_1^5x/sqrt(2x-1)dx.

:. I=1/2int_1^5{(2x-1)+1}/sqrt(2x-1)dx,

=1/2int_1^5{(2x-1)/sqrt(2x-1)+1/sqrt(2x-1)}dx,

=1/2int_1^5{sqrt(2x-1)+1/sqrt(2x-1)}dx.

Now, recall that,

intsqrttdt=2/3t^(3/2)+c_1, &, int1/sqrttdt=2sqrtt+c_2.

:. I=1/2[1/2*2/3(2x-1)^(3/2)+1/2*2sqrt(2x-1)]_1^5,

=1/2[1/3(2x-1)^(3/2)+sqrt(2x-1)]_1^5,

=1/2[{1/3(2xx5-1)^(3/2)+sqrt(2xx5-1)}]

-1/2[{1/3(2xx1-1)^(3/2)+sqrt(2xx1-1)}],

=1/2[{1/3*3^3+3}-{1/3*1+1}],

=1/2[12-4/3].

I=16/3.

Jun 18, 2018

int_1^5 x/sqrt(2x-1) dx = 16/3

Explanation:

I = int_1^5 x/sqrt(2x-1) dx

Let u = 2x-1

-> x=(u+1)/2 and dx = (du)/2

Indefinite I = int ((u+1)/2)/sqrt(u) (du)/2

= 1/4 int (u+1)/sqrtu du

= 1/4 int(u^(1/2) + u^(-1/2)) du

Apply linearity

= 1/4 int u^(1/2)du + int u^(-1/2) du

Apply power rule

= 1/4 [u^(3/2)/(3/2) + u^(1/2)/(1/2)] +C

= [u^(3/2)/6 +u^(1/2)/2]+C

Undo substitution

I= [(2x-1)^(3/2)/6 + (2x-1)^(1/2)/2]_1^5

= [(2(2x-1)^(3/2)+6(2x-1)^(1/2))/12]_1^5

= [(sqrt(2x-1)(2(2x-1)+6})/12]_1^5

= [(sqrt(2x-1)(4x-2+6))/12]_1^5

= [(sqrt(2x-1)(x+1})/3]_1^5

= ((sqrt(9)xx6)/3 - (sqrt(1)xx2)/3)

=(6-2/3) = 16/3

Jun 18, 2018

16/3

Explanation:

int_{1}^{5}x/sqrt(2x-1)dx

Let u = 2x-1

Then, 2x = u+1

\thereforex=(u+1)/2

Using this, we can say that:

(dx)/(du) = 1/2

\thereforedx=1/2du

The reason why we did all this calculation is so that we can turn

int_1^5x/sqrt(2x-1)dx

into a simpler integral of:

int_1^9(u+1)/(2sqrt(u))*1/2du

Notice that the ranges have changed. This is because the variable have changed to u instead of x. So the values have to change to be in terms of u not x.

= 1/2int_1^91/2*(u+1)/(sqrt(u))du

= 1/4int_1^9(u+1)/(sqrt(u))du

= 1/4int_1^9u/(sqrt(u)) + 1/sqrt(u)du

= 1/4int_1^9u/(sqrt(u))du + 1/4int_1^91/(sqrt(u))du

= 1/4int_1^9u^(1/2)du + 1/4int_1^9u^(-1/2)du

= 1/4[2/3u^(3/2)]_1^9 + 1/4[2u^(1/2)]_1^9

Assuming that you know how to do basic integrals, I will skip the steps to solve the above expression.

After solving the above:

= 13/3 + 1

= 16/3

Hope that makes sense! If it doesn't make sense, feel free to comment any questions.